2018
DOI: 10.1609/icaps.v28i1.13911
|View full text |Cite
|
Sign up to set email alerts
|

Aligning Partially-Ordered Process-Execution Traces and Models Using Automated Planning

Abstract: Conformance checking is the problem of verifying if the actual executions of business processes, which are recorded by information systems in dedicated event logs, are compliant with a process model that encodes the process' constraints. Within conformance checking, alignment-based techniques can exactly pinpoint where deviations are observed. Existing alignment-based techniques rely on the assumption of a perfect knowledge of the order with which process' activities were executed in reality. However, experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
0
4
0
6
Order By: Relevance
“…In [69], the authors adopt a partial order notion for the observed event data. Using this representation, the authors propose to use automated planning algorithms [70] and provide an algorithmic framework in the standardized Planning Domain Definition Language (PDDL) language.…”
Section: Certain Semanticsmentioning
confidence: 99%
“…In [69], the authors adopt a partial order notion for the observed event data. Using this representation, the authors propose to use automated planning algorithms [70] and provide an algorithmic framework in the standardized Planning Domain Definition Language (PDDL) language.…”
Section: Certain Semanticsmentioning
confidence: 99%
“…For tackling the segmentation issue, we rely on three main steps: (i) a frequent-pattern identification technique [11] to automatically derive the routine segments from a UI log (i.e., routine segments describe the different behaviours of the routine(s) under analysis, in terms of repeated patterns of performed user actions), (ii) a human-in-the-loop interaction to filter out those segments not allowed (i.e., wrongly discovered from the UI log) by any real-world routine execution by means of declarative constraints [13], and (iii) a routine traces detection component that leverages trace alignment in process mining [12] to cluster all user actions belonging to a specific routine segment into well-bounded routine traces (i.e., a routine trace represents an execution instance of a routine within a UI log). Such traces are finally stored in a dedicated routine-based log, which captures exactly all the user actions happened during many different executions of the routine.…”
Section: Smartrpa: From Ui Logs To Sw Robotsmentioning
confidence: 99%
“…For the experiments with synthetic data, we used the PLG2 [Burattin, 2015] tool to generate the event logs conforming to their respective model. We also generate four process models, with increasing sizes, according to the method used in [Leoni et al, 2018]. By size, we are talking about visible and invisible transitions.…”
Section: Synthetic Event Log and Process Modelmentioning
confidence: 99%